Science Literacy Ability and Student Learning Outcomes On Project Based Learning (PjBL) (Journal of Primary Education, 2019)
This study aimed to analyze the effectiveness of Project Based Learning in the ability of science literacy and student learning outcomes in science teaching. The research method used is quantitative in the form of an experimental quasy design with an unequal control group design. The sample in this study were fifth grade students at SDN Jambu 4 and fifth grade students at SDN 3 Sobrong. The sampling of this research used the purpose random sampling technique. Quantitative data were analyzed by t-test and gain test based on the value of scientific literacy abilities and student learning outcomes. The results showed that the average difference in students' scientific literacy skills in classes that apply the Project Based Learning model is better than classes that apply expository model (tvalue= 3.559 > ttable= 2.479); the average difference in student learning outcomes in classes that apply the Project Based Learning model is better than classes that apply the expository model (tvalue= 3.848 > ttable= 2.479); the results of increasing students' scientific literacy skills in classes that apply the Project Based Learning model are better than classes that apply expository model; the results of improved student learning outcomes in classes that apply the Project Based Learning model are better than classes that apply the expository model. The Project Based Learning model is very effective in improving the ability of scientific literacy and student learning outcomes.